Characterization of ultrastructure of the leaf surface in species of the genus Hieracium L. in the Crimean flora (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
For the first time the surface ultrastructure of leaf epidermis of 10 species of the genus Hieracium in the flora of Crimea was studied using SEM. Both common (amphystomatic features, anomocytic type of stomata, longitudinal arrangement of stomata, cuticle roll around stomata, arrangement of wax deposits) and specific characteristics of the leaf ultrastructure of the studied species have been revealed. Most of them are additional diagnostic characters on the sectional level (surface relief type, arrangement of stomata relative to the level of basal epidermal cells, presence and type of trichomes; amount of wax deposits; cell contours) and the species level (surface relief type; localization of trichomes; cell contours). The homogeneity of H. sabaudum was set.
Keywords: Hieracium, leaf, SEM, surface ultrastructure of leaves, Crimean flora.